PENGARUH PENDIDIKAN KESEHATAN PEREMPUAN MENOPAUSE TERHADAP TINGKAT KECEMASAN DI WILAYAH KERJA PUSKESMAS MERDEKA PALEMBANG - Maria, Lisda; Ety Susila Ningrum (Jurnal Kesehatan dan Pembangunan, 2025)
Menopause is the phase where the menstrual cycle stops in women, which generally occurs between the ages of 45 and 50 years. Physical and hormonal changes that accompany this period often trigger anxiety disorders, depression, and emotional instability. Health education plays an important role in reducing anxiety levels and increasing women's understanding of menopause. This study aims to evaluate the impact of providing health education on anxiety levels in women experiencing menopause. This study used a one-group pretest-posttest design. The population in this study were all visits to the Elderly polyclinic from July to September 2024, with a total of 35 people, who were also sampled using the total sampling technique. The instrument used was an anxiety questionnaire, while the intervention was in the form of counseling about menopause for seven days. Data analysis was carried out univariately and bivariately using the Wilcoxon test. The results showed that before the intervention, most respondents experienced moderate (88.6%) and mild (11.4%) anxiety. After the intervention, there was a decrease in anxiety with the results of mild anxiety (60%) and no anxiety (40%). The Wilcoxon test produced a p value = 0.000 indicating a significant effect of health education on anxiety levels in menopausal women. This finding indicates that increased knowledge can help reduce concerns arising from complaints during menopause. The majority of respondents felt calmer and more prepared to face discomfort after receiving information through health counseling. Various daily problems that have been explained in education also contribute to reducing the anxiety experienced.